Internal Conflicts in Kinan Character of Layangan Putus Movie - Wan Arida Hasanah, M. Kiki Wardana, Mayasari (CV. Pusdikra Mitra Jaya, 2023)
This study aims to analyze the internal conflict experienced by Kinan in this film. Layangan Putus (2020), directed by Beni Setiawan, written by Nur Eka Prasetyawati, and produced by Md Entertainment this film, tells the story of a wife who is defending her household, and experiences internal conflict due to her husband's infidelity. The identified data are analyzed according to Sigmund Freud's theory, in which his theory discusses the Id, Ego, and Superego. The purpose of this research is to help people understand more about what internal conflict is and realize its impact, if it is beneficial to them and those around them. surroundings. This study uses qualitative research to describe the internal conflicts that occur. to support the author's analysis using books, theses, journals, and series Layangan Putus from the platform: WeTv as a data source. From this study, the authors found that there were 4 internal conflicts experienced by Kinan that pushed the id, ego, and superego to act. Internal conflicts are found by the characters in the film Layangan Putus, and the internal impact of the conflicts contained in the film is. heavy considerations and doubts so that his subconscious leads the Id, Ego and Superego to act. that what internal conflicts do to the id, ego, and superego that can lead to right or wrong decisions.